Specific phytocannabinoid compositions are associated with analgesic response and adverse effects in chronic pain patients treated with medical cannabis. (July 2021) - Aviram, Joshua; Lewitus, Gil M.; Pud, Dorit; Procaccia, Shiri; Berman, Paula; Yellin, Ben; Vysotski, Yelena; Hazan, Or; Eisenberg, Elon; Meiri, David
Abstract: Medical cannabis (MC) treatment for chronic pain is increasing, but evidence regarding short- and long-term efficacy and associated adverse effects (AEs) of the different cannabis plant components is limited. Most reports focus on two phytocannabinoids, (-)-Δ 9 - trans -tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD). This study, aimed to identify patterns of phytocannabinoid compositions associated with MC treatment response and with related AEs. Participants in this multicenter prospective cohort were patients with chronic non-cancer pain that were prescribed MC by physicians. Data was collected before MC treatment, at one month (short-term) and at 12 months (long-term). Simultaneously, liquid chromatography mass spectrometry identification and quantification of phytocannabinoids from the cultivars were performed. The monthly dose of each phytocannabinoid for each patient was z-scaled and clustered into ten groups to assess the difference in analgesic treatment response (≥30%/50% pain intensity reduction) and AEs rates. We identified ten clusters that had similar analgesic treatment response rates. However, there were significant differences in AEs rates both at short- and long-term. We identified specific phytocannabinoid compositions that were associated with overall AEs rates (5% compared to 53% at short-term and 44% at long-term) and with specific AEs rates such as MC related central nervous system, gastrointestinal and psychological AEs. To conclude, Evaluating only Δ9-THC or CBD is insufficient to find associations with MC related AEs. Therefore, comprehensive profiling of phytocannabinoids is needed to discover associations to related AEs and help physicians prescribe safer cannabis with less AEs while still relieving pain. Graphical Abstract: ga1 Highlights: Medical cannabis (MC) is gaining momentum as a leading treatment for chronic pain. Studies demonstrated that MC treatment is effective and has a wide safety margin. High-THC and High-CBD strains are similarly effective in reducing pain. Specific phytocannabinoid compositions are associated with more adverse effects. This work provides tools for physicians to prescribe MC with less adverse effects.